Kyrgyz Republic Public Expenditure Review Policy Notes : Strategic Setting - World Bank (Washington, DC, 2014)
The current approach to fiscal policy is delivering suboptimal outcomes for the citizens of the Kyrgyz Republic. The past five years have been difficult for the Kyrgyz Republic, with one shock following another. Government spending ballooned to 39 percent of GDP in 2012 one of the highest ratios among developing countries globally, as the authorities tried to mitigate the shocks. However, despite increases in spending, the quality of health services remains poor; above 80 percent of 15 year-olds are classified as illiterate; wages in the public sector are low; and only 6 percent of social assistance reaches the poorest members of society. In addition, risks are mounting in the pension system, few instruments exist to support the vulnerable and the physical capital stock is depreciating, especially in the energy sector. This Public Expenditure Review (PER) focuses on the effectiveness, level, and composition of public spending in number of sectors. The objective of this synthesis note is to better understand the overall environment for fiscal policy as well as the nature and composition of public revenues and expenditures. The sectoral policy notes review the challenges and options in specific sectors, namely, education, health, pensions, social protection, and energy as well as cross-cutting themes such as the wage-bill and public investment management and intergovernmental relations. While more detailed sector-specific recommendations are contained in the sectoral policy notes, more general recommendations on fiscal policy will also contribute to sustainable fiscal consolidation.